Patterns of use of oral anticancer treatments in France: a Retrospective Analysis of Cancer Treatments given ORally from 2004 to 2012 (Re-ACTOR study). (February 2015) - Benjamin, L.; Maroun, R.; Maurel, F.; Bardoulat, I.; Ricarte, C.
Abstract Backgrounds and objectives: Increasing use of oral anticancer treatments (OATs) in oncology is modifying the treatment paradigm for cancer. Nonetheless, available data on the pattern of use of OATs and its evolution over time are limited. The objective of this study was to describe the patterns of use of OATs in France from 2004 to 2012. Methods: A retrospective analysis was performed using Oncology Analyzer, a physician survey database. All patients actively treated by an oral or an intravenous anticancer treatment between October 2004 and September 2012 were enrolled in the database. Descriptive analyses were performed by treatment category with a focus on the last year of collection and the evolution across the study period. Results: From October 2011 to September 2012, a sample of 7426 patients treated by oral or intravenous active anticancer treatments was analyzed: 74% of patients receiving an OAT were diagnosed with a solid tumor, 52% of whom had a stage IV cancer. The use of OATs increased with age and was the highest in patients over 80 years. From 2004 to 2012, the proportion of cancer patients receiving OATs increased by four percentage points (from 28.4% to 32.5%). Additionally, for treatments available in both forms, a marked preference for oral formulations was observed. Limitations: The patterns and trend of use prior to 2004 were not addressed due to lack of information in the database. The use of a market research database is relevant for highly prevalent cancers but for rare cancers the sample size is limited, underlining the utility of using other data sources such as cancer registries. Conclusions: The Re-ACTOR study provides an overview of OAT use in France, which was prescribed to 32% of cancer patients in France in 2012, principally to older patients and to those with solid tumors and with metastatic disease.